Guía y herramienta computacional para el diseño hidráulico de un sistema de tratamiento preliminar (cribado y desarenador) de aguas residuales. (2017)
The present work contains the description, technical considerations, methodologies of calculation and the application guide of a computational tool for the design of the processes of preliminary treatment of residual waters: screening and desanding.The application of this computational tool is based on the hydraulic analysis that requires the design of the preliminary wastewater treatment.